Curcumin mimics of potential chemoprevention with NQO1 induction properties - Dalia R. Aboshouk; Ahmed R. Hamed; Siva S. Panda; Mohamed S. Bekheit; M. Adel Youssef; Adel S. Girgis (Scientific Reports)
Abstract Chemoprevention is one of the accessible strategies for preventing, delaying or reversing cancer processing utilizing chemical intervention of carcinogenesis. NAD(P)H quinone oxidoreductase 1 (NQO1) is a xenobiotic metabolizing cytosolic enzyme/protein with important functional properties towards oxidation stress, supporting its ability in detoxification/chemoprotective role. A set of 3,5-diylidene-4-piperidones (as curcumin mimics) bearing alkyl sulfonyl group were synthesized with potential NQO1 induction properties. Compounds 5ab (R = 2-MeOC6H4, R’ = Me) and 5ac (R = 2-MeOC6H4, R’ = Et) are the most promising agents synthesized (% induction of NQO1 = 51.562, 45.793) relative to that of 4’-bromoflavone (4’-BF, reference standard) at 10 µM. LPS-induced iNOS production in RAW264.7 macrophages of the most promising agents discovered (5ab and 5ac) displayed concentration-dependent with comparable activities to the reference anti-inflammatory drug indomethacin. Molecular modeling studies (including QSAR, molecular docking and molecular dynamics) were accessed supporting the observed biological profiles.